PENERAPAN SISTEM INFORMASI BARANG PENDING BERBASIS WEB DI PT SUGINDO INTERNATIONAL - Hermawati, Karmila; Rivatunisa, Cyntia (POLITEKNIK PIKSI GANESHA, 2025)
In today’s digital era, the use of information technology is essential to improve work efficiency andeffectiveness across various sectors, including the industrial sector. PT Sugindo International previouslyemployed a manual method using paper- based forms to report problematic (abnormal) products thatrequired decisions from the Quality Control (QC) department. This method was considered inefficient andprone to data loss and delays in information delivery. This study aims to design and implement a web-basedinformation system that enables operators to input data on abnormal products to be placed in a pendingarea, and allows QC to provide decisions regarding those products. The system is designed to be accessibleonly to company employees through a login process based on their respective departments, therebymaintaining data security and confidentiality. The system was developed using a UML modeling approach,including use case and activity diagrams. The results show that the system significantly improves the speed,efficiency, and documentation of the reporting and handling process of pending products. Moreover, itenhances real-time coordination between the production and QC departments without relying on paperbasedcommunication.